On the numerical simulation of stagnation point flow of non-Newtonian fluid (Carreau fluid) with Cattaneo-Christov heat flux. (April 2020) - Ijaz Khan, M.; Nigar, Mehr; Hayat, T.; Alsaedi, A.
Highlights: Here Cattaneo-Christov (CC)heat is studied in flow of Carreau fluid. MHD stagnation point flow is considered. Both stretching and shrinking effects are considered. CC model is used instead of Fourier law. Abstract: Background: This research article is devoted to evaluating the impact of Cattaneo-Christov heat in MHD stagnation point flow over a stretched and shrinking surface of the cylinder. MHD liquid of Carreau fluid is considered. Flow is generated due to stretching and shrinking aspects. The energy equation is developed in the presence of Cattaneo-Christov heat flux, where thermal relaxation time plays an important role in the heat transport. Method: The appropriate transformations are employed to solve a differential system via shooting method (bvp4c). Results: The velocity, skin friction coefficient, temperature and Nusselt number are discussed versus different pertinent flow variable graphically. Over results indicate that the velocity distribution decreases against larger magnetic power law index and Weissenberg number. Temperature field diminishes via Prandtl number and thermal relaxation variable. Engineering quantities are discussed graphically. Magnitude of skin friction or velocity gradient upsurges versus magnetic parameter. Moreover, temperature gradient or Nusselt number shows the increasing impact via Prandtl number. Main observations of the considered flow problem are listed as concluding remarks.